WEB BASED FINAL EXAMINATION SCHEDULING SYSTEM - Phang, Min Hui (Universiti Malaysia Sarawak, (UNIMAS), 2015)
This study,focuses on solving faculty- final examination scheduling problem. The heuristic method is proposed to solve the scheduling problem. There are two stages of algorithm to solve the problem, which are course grouping and timeslot and venue allocation. The stage of course grouping is to minimize the complexity of the problem. After the course grouping, the stage of timeslot and venue allocation is applied to generate a good quality of final examination timetable.